Application of novel Fe3O4/Zn-metal organic framework magnetic nanostructures as an antimicrobial agent and magnetic nanocatalyst in the synthesis of heterocyclic compounds - Bashar, Bashar S.; Kareem, Hawraa A.; Hasan, Yaser Mohamed; Ahmad, Nafis; Alshehri, A. M.; Al-Majdi, Kadhum; Hadrawi, Salema K.; AL Kubaisy, Munthir Mohammed Radhy; Qasim, Maytham T. (Frontiers in Chemistry, 2022)
Using the microwave-assisted method, novel Fe3O4/Zn-metal organic framework magnetic nanostructures were synthesized. The crystallinity, thermal stability, adsorption/desorption isotherms, morphology/size distribution, and magnetic hysteresis of synthesized Fe3O4/Zn-metal organic framework magnetic nanostructures were characterized by XRD patterns, TGA curve, BET adsorption/desorption technique, SEM image, and VSM curve, respectively. After confirming the Fe3O4/Zn-metal organic framework magnetic nanostructures, its antimicrobial properties against Gram-positive bacterial, Gram-negative bacterial, and fungal strains based on minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and minimum fungicidal concentration (MFC) values were studied. The MIC values in antimicrobial activity for Gram-positive and Gram-negative bacterial strains, between 16–128 μg/ml, and for fungal strain, 128 μg/ml were observed. The results showed that the high specific surface area of Fe3O4/Zn-metal organic framework magnetic nanostructures caused the antimicrobial power of nanoparticles to be high, and the observed antimicrobial effects were higher than some known commercial antimicrobial drugs. Another advantage of the specific surface area of Fe3O4/Zn-metal organic framework magnetic nanostructures was its high catalytic properties in the three-component reaction of isatin, malononitrile, and dimedone. New spiro [indoline-pyranopyrimidines] derivatives were synthesized with high efficiency. The catalytic activity results of Fe3O4/Zn-metal organic framework magnetic nanostructures showed that, in addition to recyclability, derivatives could be synthesized in less time than previously reported methods. The results of investigating the catalytic activity of Fe3O4/Zn-metal organic framework magnetic nanostructures showed that the spiro [indoline-pyranopyrimidines] derivatives were synthesized in the time range of 10–20 min with an efficiency of over 85%. As a final result, it can be concluded that the microwave synthesis method improves the unique properties of magnetic nanostructures, especially its specific surface area, and has increased its efficiency.